Clarithromycin use and the risk of mortality and cardiovascular events: A systematic review and meta-analysis - You, Ching-Hui (PLoS One, 2019)
BACKGROUND: Although studies reported increased cardiovascular (CV) risks in patients treated with macrolides, the risks remain controversial among clarithromycin (CLR) users. We aimed to summarize the association between CLR use and the risks of mortality and CV events. METHODS: We searched PubMed, EMBASE, Web of Science, and the Cochrane Library for randomized controlled trials (RCTs) and observational studies with population exposed to CLR published until December 31(st), 2018. These studies reported either all-cause mortality (primary outcome) or CV adverse events (secondary outcomes) based on multivariate models. Effect measures were synthesized by study design and follow-up duration (long-term, ≥ 1 year; short-term, ≤ 3 months; and immediate, ≤ 2 weeks). This study has been registered on PROSPERO (ID: CRD42018089605). RESULTS: This meta-analysis included 13 studies (3 RCTs and 10 observational studies) and 8,351,815 subjects (1,124,672 cases and 7,227,143 controls). Overall, CLR use was not associated with increased long-term all-cause mortality (pooled rate ratio RR = 1.09, 95% CI = 0.91–1.32), either among patients with or without comorbidities of cardiovascular diseases. Comparing CLR users to placebo, there is no additional risks of cardiac mortality (pooled RR = 1.03, 95% CI = 0.53–2.01), acute myocardial infarction (pooled RR = 1.29, 95% CI = 0.98–1.68), and arrhythmia (pooled RR = 0.90, 95% CI = 0.62–1.32). CONCLUSIONS: Our findings suggested no significant association between CLR use and subsequent long-term all-cause mortality, regardless having comorbidity of cardiovascular diseases or not. Further RCTs investigating the short-term CV risks of CLR use compared to alternative antibiotics are warranted, particularly in high-risk populations.